Adaptación de lentes de contacto multifocal en paciente présbita de 43 años. - Moya García, Carmen Daniela (2023)
The present clinical case study addresses the issue of the adaptation of multifocal contact lenses in a 43-year-old presbyopic patient. Taking as a starting point that presbyopia is a refractive error, in most cases it occurs after the age of 40, it is totally physiological and affects visual and optical quality. To adapt the contact lenses it was necessary to determine parameters such as the final dioptric power of the lens, diameter and base curve. Preadaptation tests were performed such as visual acuity, objective and subjective refraction, biomicroscopy, ophthalmoscopy, Schirmer test and tear breakup time (BUT), which allowed us to know the patient's refractive status, ocular physiology and the quality and quantity of the tears. . . The results obtained demonstrated that the patient is suitable to be a contact lens user because he has an optimal tear film. Taking into account the activities carried out by the patient, we are looking for a soft contact lens with certain characteristics such as silicone hydrogel material, high wetting and HIGH (DK/T). Therefore, an ALCOM multifocal contact lens was determined with its respective measurements, a diameter of 14.0mm and a base curve of 8.6. He gained greater comfort when carrying out his work activities since after the rhinoplasty operation he could not use aerial lenses for 6 weeks. Multifocal contact lenses seem very practical, you have more clarity in peripheral vision and aesthetics.